ENGLISH TITLE TRANSLATION ON IMDB OF INDONESIAN ROMANCE MOVIES RELEASED FROM 2020 TO 2024 - Raden Roro Shinta Felisia (Asosiasi Dosen Muda Indonesia, 2024)
Movie titles are also accessible through the